2023
DOI: 10.2807/1560-7917.es.2023.28.4.2200340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuraminidase inhibitor (oseltamivir) treatment on outcome of hospitalised influenza patients, surveillance data from 11 EU countries, 2010 to 2020

Abstract: Background Timely treatment with neuraminidase inhibitors (NAI) can reduce severe outcomes in influenza patients. Aim We assessed the impact of antiviral treatment on in-hospital deaths of laboratory-confirmed influenza patients in 11 European Union countries from 2010/11 to 2019/20. Methods Case-based surveillance data from hospitalised patients with known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…Dominguez et al [ 23 ], in a study of 1727 hospitalized patients in Catalonia, reported a reduced mortality risk (aOR = 0.37; p < 0.001) for patients receiving NAI treatment in the first 48 h after clinical symptom onset. Similar results have been observed in a surveillance data survey conducted in 11 European countries [ 24 ]. Nonetheless, despite the evidence available on the effectiveness of antivirals in preventing severity, several barriers to their systematic use exist and clinical practice is quite variable [ 13 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Dominguez et al [ 23 ], in a study of 1727 hospitalized patients in Catalonia, reported a reduced mortality risk (aOR = 0.37; p < 0.001) for patients receiving NAI treatment in the first 48 h after clinical symptom onset. Similar results have been observed in a surveillance data survey conducted in 11 European countries [ 24 ]. Nonetheless, despite the evidence available on the effectiveness of antivirals in preventing severity, several barriers to their systematic use exist and clinical practice is quite variable [ 13 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Controlling for the effect of antiviral treatment, in our study, a history of vaccination was 15% effective in reducing the pneumonia risk in severe cases of influenza, a finding similar to that observed in other studies [20][21][22][23][24][25][26][27]. While this result may, on the face of it, seem to be less than spectacular, it needs to be considered in a context of pneumonia representing a greater risk of ICU admission and death for our patients, despite their relatively younger age and despite the greater severity profile for the control group due to higher rates of obesity, COPD, and ARDS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation